Prevalence of livestock-associated MRSA in communities with high pig-densities in The Netherlands. - Brigitte A van Cleef (PLoS ONE, 2010)
BACKGROUND: Recently, livestock-associated methicillin-resistant Staphylococcus aureus CC398 has been discovered in animals, livestock farmers and retail meat. This cross-sectional study aimed to determine the spread to persons not in direct contact with livestock in areas with a high density of pig farms. METHODOLOGY/PRINCIPAL FINDINGS: With a random mailing in 3 selected municipalities in The Netherlands, adult persons were asked to fill in a questionnaire and to take a nose swab. In total, complete information was obtained on 583 persons. Of the 534 persons without livestock-contact, one was positive for MRSA (0.2%; 95% confidence interval, <0.01-1.2). Of the 49 persons who did indicate to be working at or living on a livestock farm, 13 were positive for MRSA (26.5%; 95% confidence interval, 16.1-40.4). All spa-types belonged to CC398. CONCLUSIONS/SIGNIFICANCE: Livestock-associated MRSA has a high prevalence in people with direct contact with animals. At this moment it has not spread from the farms into the community.